GMINOWŁADZTWO LELEWELA CZY FEUDALIZM KARAMZINA – USTRÓJ PANUJĄCY NA OBSZARZE RUSI W ŚREDNIOWIECZU - Eligiusz Podolan (In Gremium. Studies in History, Culture and Politics, 2008)
MEDIEVAL RUTHENIA’S SOCIAL SYSTEM ACCORDINGTO LELEWEL AND KARAMZIN:LOCAL GOVERNANCE OR FEUDALISM?S u m m a r yThis paper deals with the social systems in medieval Poland and Ruthenia – as described by scholars of theEnlightenment: Joachim Lelewel and Mikołaj Karamzin. The former sees the Slavic lands as dominatedby the local governance of the noblemen, with a high share of hereditary, rather than vassal, lands. Thelatter stresses the influence of feudalism on the development of Ruthenia’s social system because he iskeen on erasing the technological and historical differences between present-day Russia and WesternEurope. This paper’s author sets out to show the influence of the changing feudal system on the developmentof Central European countries.